Local Production of the Alternative Pathway Component Factor B Is Sufficient to Promote Laser-Induced Choroidal Neovascularization - Schnabolk, Gloriane (Invest Ophthalmol Vis Sci, 2015)
PURPOSE. Complement factor B (CFB) is a required component of the alternative pathway (AP) of complement, and CFB polymorphisms are associated with age-related macular degeneration (AMD) risk. Complement factor B is made in the liver, but expression has also been detected in retina and retinal pigment epithelium (RPE)-choroid. We investigated whether production of CFB by the RPE can promote AP activation in mouse choroidal neovascularization (CNV). METHODS. Transgenic mice expressing CFB under the RPE65 promoter were generated and crossed onto factor B-deficient (CFB-KO) mice. Biological activity was determined in vitro using RPE monolayers and in vivo using laser-induced CNV. Contribution of systemic CFB was investigated using CFB-KO reconstituted with CFB-sufficient serum. RESULTS. Transgenic mice (CFB-tg) expressed CFB in RPE-choroid; no CFB was detected in serum. Cultured CFB-tg RPE monolayers secreted CFB apically and basally upon exposure to oxidative stress that was biologically active. Choroidal neovascularization sizes were comparable between wild-type and CFB-tg mice, but significantly increased when compared to lesions in CFB-KO mice. Injections of CFB-sufficient serum into CFB-KO mice resulted in partial reconstitution of systemic AP activity and significantly increased CNV size. CONCLUSIONS. Mouse RPE cells express and secrete CFB sufficient to promote RPE damage and CNV. This further supports that local complement production may regulate disease processes; however, the reconstitution experiments suggest that additional components may be sequestered from the bloodstream. Understanding the process of ocular complement production and regulation will further our understanding of the AMD disease process and the requirements of a complement-based therapeutic.